The DIR/Floortime Approach to Enhance Communication Skills of Autism Student in Inclusive Elementary Schools - Sinyanyuri, Sonya; Supena, Asep; Bintoro, Totok (CV. Rayyan Dwi Bharata, 2024)
This research aims to explore the DIR/Floortime approach implemented by teachers to enhance the communication abilities of children with autism in inclusive elementary schools. The type of research used is a qualitative descriptive design with a case study methode. The subjects of this study were teacher who teach achildren with autism attending an inclusive school, at Lazuardi GCS Elementary School in Depok City. The results of the research indicate that the DIR/Floortime approach carried out by teachers involves using a play-based approach conducted on the floor (floortime). This is methode provide opportunities for students to engage, enhance self-confidence, and foster a sense of blending in for children with autism with their environment.